If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 5) = -1 Reorder the terms: 2(5 + x) = -1 (5 * 2 + x * 2) = -1 (10 + 2x) = -1 Solving 10 + 2x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 2x = -1 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = -1 + -10 2x = -1 + -10 Combine like terms: -1 + -10 = -11 2x = -11 Divide each side by '2'. x = -5.5 Simplifying x = -5.5
| X+4=-47 | | -7a+5+8a=5-23 | | 5-2x=-4x-2 | | 48/1-9/5= | | -3+2(-2)=1+4(-2) | | -3y=-6x+9 | | (x-1)^(2/3)=64 | | X+3=-71 | | 4x^(9/2)-20=0 | | 60x-y-80=0 | | 60x+y+80=0 | | 5cos(x)+5sin(x)=5 | | 6h+73=46 | | 4ln(20/0) | | 13z-1=14z-6 | | 4a+2b=39 | | 5=y/3--9 | | 4.9x^2-65x-115=0 | | 8n-4=4 | | 15=2m+4 | | x+111=99 | | x-44=0 | | 12x+3=7x+5 | | f(x)=2x^5-5x^4 | | 8x^6y^2+4x^6y^2= | | 8x^6+4x^6= | | 4sqrtx-6=8 | | 30xy^2+x^2y-6x=0 | | h+3.6=0.2 | | 33=12r-3(9+r) | | r-51.6=10 | | n=m+15form |